061 QT prolongation associates with increased mortality in patients with rheumatoid arthritis. (16th May 2012) - Panoulas, V F; Toms, T E; Metsios, G S; Stavropoulos-Kalinoglou, A; Sandoo, A; Douglas, K M J; Kitas, G D
Abstract : Background: Rheumatoid arthritis (RA) has been linked with increased cardiovascular morbiditly and sudden cardiac death (SCD). A mechanistic link between prolonged QTc and increased risk of fatal arrhythmogenesis is well established. In the general population, there is no consistent evidence for increased risks of total or cardiovascular mortality or SCD in patients with modest prolongation of the QTc interval. The present study examines the presence of an association between prolonged QTc and mortality in RA patients. Methods: A cohort of 377 RA patients with detailed clinical and biochemical characterisation and baseline ECGs was followed-up prospectively. The QT interval lengths were corrected for heart rate using Bazett's Formula. The association of QTc with total mortality was assessed using Cox proportional hazards regression analysis. Patients with atrial fibrillation, flutter or bundle branch block were excluded from the analysis. There were no patients on QT prolonging medications. Results: The mean age of the study population was 61.2 ±12.1 years, 276 (73.2%) were females, the mean QTc was 427.3±24.4 ms and the mean QRS 91.9±23.8 ms. Of the 377 patients a total of 50 (13.3%) died during the follow-up period (63.5±15.7 months or 1994 person-years). Survival analysis revealed a crude HR of 1.20 (95% CI 1.07 to 1.33, p=0.002) per 10 ms increase in QTc. When adjusting for age, gender, smoking status, BMI, presence of hypertension, dyslipidaemia or insulin resistance HR per 10 ms increase in QTc remained significantly associated with total mortality 1.12 (95% CI 1.002 to 1.25, p=0.045). After adjustment for QRS and presence of LVH the HR was 1.17 (95% CI 1.01 to 1.34, p=0.035). Further adjustment for disease severity specific parameters including steroid exposure, anti-RF, anti-CCP antibodies and CRP did not alter the above association. ROC curve analysis determined a QTc cut-off for increased mortality at 426.5 ms (AUC 0.634, p=0.002). The crude HR for overall mortality for RA patients at the prolonged QTc group (≥426.5 ms), was 2.65 (95% CI 1.45 to 4.85, p=0.002). Conclusions: Prolongation of QTc associates with an increased risk of death in patients with RA. This association remains significant after adjustment for established cardiovascular risk factors and markers of disease severity.